2008
DOI: 10.1542/peds.2007-2022rr
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus in Greek Children With Respiratory Tract Infection

Abstract: INTRODUCTION: Human bocavirus (family Parvoviridae) was recently identified in children with respiratory tract infection (RTI), first in Sweden, and subsequently in different parts of the world. OBJECTIVE: The aim of our study was to gain insight into the epidemiology of bocavirus in children with RTI in Greece. METHODS: One hundred ten throat-swab samples were collected during the autumn and winter months of 2006–2007 from previously healthy children (aged 1 month to 13 years) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 0 publications
3
19
0
4
Order By: Relevance
“…Clinical studies in Taiwan could associate low lymphocyte counts with respiratory failure [39]. In children, thrombocytosis occurs commonly in infections of the lower respiratory tract though an indicative correlation could not be identified [40]. In humans, the ratio of neutrophils to lymphocytes was also suggested as a diagnostic indicator for differentiating pH1N1 infections from other influenza-like illnesses [41].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies in Taiwan could associate low lymphocyte counts with respiratory failure [39]. In children, thrombocytosis occurs commonly in infections of the lower respiratory tract though an indicative correlation could not be identified [40]. In humans, the ratio of neutrophils to lymphocytes was also suggested as a diagnostic indicator for differentiating pH1N1 infections from other influenza-like illnesses [41].…”
Section: Discussionmentioning
confidence: 99%
“…Subramaniam et al, indicated that respiratory infection was the predominant (28.3%) infectious cause of reactive thrombocytosis (5). Hadidopulou found reactive thrombocytosis in children with viral respiratory tract infection (6). However, Wolach et al, found thrombocytosis in children with pneumonia and empyema (7).…”
Section: Introductionmentioning
confidence: 99%
“…Siempre se debe confirmar con un nuevo hemograma, dado que existen situaciones que pueden hacer que el recuento plaquetario se vea falsamente aumentado (crioglobulinemia mixta o lisis celular) 1,4,5 . Siempre se debe confirmar con un nuevo hemograma, dado que existen situaciones que pueden hacer que el recuento plaquetario se vea falsamente aumentado (crioglobulinemia mixta o lisis celular) 1,4,5 .…”
Section: Discussionunclassified
“…En este aspecto, y ya desde el ingreso, una anamnesis dirigida (tabla 2), una adecuada interpretación de las pruebas complementarias (tabla 3) y una exhaustiva exploración física (descartando la presencia de visceromegalias o adenopatías) permiten orientar el diagnóstico 1,3,4 . En este aspecto, y ya desde el ingreso, una anamnesis dirigida (tabla 2), una adecuada interpretación de las pruebas complementarias (tabla 3) y una exhaustiva exploración física (descartando la presencia de visceromegalias o adenopatías) permiten orientar el diagnóstico 1,3,4 .…”
Section: Discussionunclassified
See 1 more Smart Citation